Investigation of catalytic oxidation of 4-nitroethylbenzene by ozone to 4-nitroacetophenone – an intermediate in the synthesis of antibiotics - A. H. Halstyan; A. S. Bushuiev (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
4-Nitroacetophenone is an important intermediate for the manufacture of broad-spectrum antibiotics, in particular chloramphenicol. Existing methods of ketone synthesis are imperfect. The disadvantage of the simplest of them (the oxidation of 4-nitroethylbenzene by oxygen at atmospheric pressure and temperature of 135 °C, in the presence of manganese oxide) is the low yield and the need for the process in a heterogeneous environment. Therefore, the development of affordable and inexpensive ways to obtain 4-nitroacetophenone is an actual task.